Reclassification of Traditional and Modern Dayah in Aceh from The Perspective of Systems Theory - Ahmad Ridha (Winaya Inspirasi Nusantara Foundation, 2020)
Dayah is an Islamic educational institution that has developed in Aceh since the time of the entry of Islam in Samudera Pasai. This institution has contributed a lot to the development of Aceh until now, but this development occurs during the modernization period, it does not rule out the possibility that this change will make a modern-based dayah curriculum systematic according to the situation and conditions of the times, thus several Islamic education institutions that are almost similar to dayah in the characteristics of identity. This change does not make that all dayah in Aceh will change by itself, there may be some dayah that are still dayah concepts in the past there are those that are in the present. That's where the illustration comes out that not all dayahs show the same, but there are several factors of curriculum systematics that distinguish what is called traditional and modern. The main indicator in solving this problem the author analyzes the anatomy of social system theory, why!!! Because the curriculum system will be seen with the internal and external structure of the system, they gave birth to the curriculum system. This is proven by the anatomy of the system that classical and sorongan learning cannot be made a difference and the curriculum guidelines for dayah institutions are all the same, the author finds that their differences can only be measured from the surface structure of the system components. In anatomy, the dayah system approach is categorized into two parts, namely: first, traditional Dayah is a dayah that has integrity in the systematic curriculum for learning classical books (Fiqh science, Sufism Science, Tauhid Science), but not all classical books, classical books that have been determined which have reference references to Abuya Muda Wali AlKlalidy. Second, modern Dayah is a dayah that has a dynamic nature in acting and making policies that do not have to limit classical books. So, this research seeks to be a source of reference, especially for dayah institutions themselves.